Self-perception of women after mastectomy as an ego defence mechanism. Comparison with a group of healthy women - Mącik, Dorota; Ziółkowska, Patrycja; Kowalska, Monika (Contemporary Oncology/Współczesna Onkologia, 2012)
Aim of the study : Analysis of changes in self-perception in post-mastectomy patients and its comparison with self-perception of healthy women. Material and methods : The subjects of this study were 50 women. The main group was post-mastectomy patients involved in the meetings of the Amazons Club (25 women). The reference group consisted of 25 healthy women. The method used in the study was the ACL (Adjective Check List) test, identifying 37 dimensions of self-image. Oncological patients completed a test twice (for current and pre-cancer self-image), and healthy women once – for current self. Both groups were selected similarly in respect of education level for the purpose of ensuring a similar level of insight. Results : Retrospective self-image and the current one in the Amazon women group were highly convergent. Existing differences include a reduced need for achievement and dominance, and a low-er level of self-confidence. However, the comparison of current self-images in both groups showed a large discrepancy of the results. The Amazon women assess themselves in a much more negative way. Also, their self-image is self-contradictory in certain characteristics. Conclusions : Mastectomy is a difficult experience requiring one to re-adapt and to accept oneself thereafter. The way of thinking about oneself is a defence mechanism helping to cope. The work with patients programmes must, therefore, focus on identifying their emotions and thoughts, especially on those they do not want to accept because of the perceived pressure from the environment to effectively and quickly deal with this difficult situation. The increasing acceptance of personal limitations may help the affected women to adjust psychologically faster and easier.